Sufi journey in Richlatu Ibn Fathumati by Najib Machfouzh (Carl Thompson's Travel Literature Analysis) - Imam Wicaksono; Sangidu; Fadlil Munawwar Manshur; Sherif Sa'ad al-Gayyar (Arabic Education Department, Islamic Studies Faculty, Universitas Muhammadiyah Malang, 2023)
This study aimed to understand the story of the journey of Sufi adherents while on a spiritual journey exploring several countries in the novel Richlatu-Ibnu Fathumati by Najib Machfouzh. This research used Carl Thompson's (2011) travel writing theory approach, which has three basic principles: reporting the world, revealing the self, and representing the other. The results of the study show that the Qandil journey is presented in three forms: (1) reporting the world in the form of stories about the conditions of the surrounding environment in the form of buildings, communities, and the natural surroundings; (2) revealing the self in the form of Qandil's feelings, emotions, and reactions during the trip. (3) representing the other: the reality of life at the place where Qandil stopped during the trip, which turned out to be a different culture from the cultural reality he had encountered in his home country. This research becomes important when the background of the traveller turns out to influence three narrative forms: reporting the world, revealing the self, and representing the other.